French River Scene - Charles-François Daubigny (Wikimedia Commons, 1871)
Oeuvre issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: French River Scene.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons